PENGARUH FAKTOR EKSPOSI TERHADAP KUALITAS CITRA RADIOGRAFI - eif sparzinanda; Nehru Nehru; nurhidayah nurhidayah (JOURNAL ONLINE OF PHYSICS, 2017)
The research on the influence of exposure factor on radiographic image quality has been conducted. This research uses phantom, water in plastic container as human substitute with focus film distance (FFD) 100 cm and broad field of irradiation 15 cm × 15 cm. The exposure conditions are given by exposure factors including variations in tube voltages of 60 kV, 65 kV, 70 kV, 75 kV, 80 kV called standard techniques or routine voltage techniques and the time flow is as big as 20 mAs, 25 mAs and 30 mAs. The results showed that the image quality will decrease with the use of current and time high. Image quality can be seen on gray-level histogram using java Image-J Basics version 1.38 software to get optimum value from exposure factor on image quality.